Characterization, dietary habits and nutritional intake of omnivorous, lacto-ovo vegetarian and vegan runners – a pilot study - Josefine Nebl (BMC Nutrition, 2019)
Abstract Background The number of people preferring plant-based nutrition is growing continuously in the western world. Vegetarianism and veganism are also becoming increasingly popular among individuals participating in sport. However, whether recreationally active vegetarian and vegan populations can meet their nutritional needs is not clear. Methods The purpose of this cross-sectional study was to compare the nutrient intake of omnivorous (OMN, n = 27), lacto-ovo vegetarian (LOV, n = 25) and vegan (VEG, n = 27) recreational runners (two to five training sessions per week) with intake recommendations of the German, Austrian and Swiss Nutrition Societies (Deutsche, Österreichische und Schweizerische Gesellschaften für Ernährung, D-A-CH) for the general population. Lifestyle factors and supplement intake were examined via questionnaires; dietary habits and nutrient intake were determined based on 3-day dietary records. Results More than half of each group did not reach the recommended energy intake (OMN: 10.4, 8.70–12.1; LOV: 9.67, 8.55–10.8; VEG: 10.2, 9.12–11.3 MJ). Carbohydrate intake was slightly below the recommendations of > 50 EN% in OMN (46.7, 43.6–49.8 EN%), while LOV (49.4, 45.5–53.3 EN%) and VEG (55.2, 51.4–59.0 EN%) consumed adequate amounts (p = 0.003). The recommended protein intake of 0.8 g/kg body weight (D-A-CH) was exceeded in all three groups (OMN: 1.50, 1.27–1.66; LOV: 1.34, 1.09–1.56; VEG: 1.25; 1.07–1.42 g/kg BW; p = 0.047). Only VEG (26.3, 22.7–29.8 EN%) did not achieve the recommended fat intake of 30 EN%. The supply of micronutrients, such as vitamin D and cobalamin, was dependent on supplement intake. Additionally, female OMN and LOV achieved the recommended daily intake of 15 mg iron only after supplementation, while VEG consumed adequate amounts solely via food. Conclusion All three groups were sufficiently supplied with most nutrients despite the exceptions mentioned above. The VEG group even showed advantages in nutrient intake (e.g. carbohydrates, fiber and iron) in comparison to the other groups. However, the demand for energy and several macro- and micronutrients might be higher for athletes. Thus, it is also necessary to analyze the endogenous status of nutrients to evaluate the influence of a vegetarian and vegan diet on the nutrient supply of athletes. Trial registration German Clinical Trial Register (DRKS00012377), registered on April 28, 2017.